IMPACTS OF CONSTRUCTION ACTIVITIES ON THE ENVIRONMENT: THE CASE OF GHANA - Simon Ofori AMETEPEY; Samuel Kwame ANSAH (Journal of Construction Project Management and Innovation)
Construction activities impact on the environment throughout the life cycle of development. These impacts occur from initial work on-site through the construction period, operational period and to the final demolition when a building comes to an end of its life. Even though the construction period is comparatively shorter in relation to the other stages of a building’s life, it has diverse significant impacts on the environment. This study investigates the major impacts of construction activities on the environment in Ghana. Thirty-three possible impacts of construction activities on the environment were identified from literature. These impacts were further categorized into nine major groups and were subjected to a cross-sectional survey. Questionnaire and interview were used to elicit the views of respondents. Questionnaires were distributed to 100 randomly selected construction practitioners made up of 58 architects, 37 quantity surveyors and 5 structural engineers registered with their professional bodies. Semi-structured interview was conducted amongst purposively selected contractors and consultants. The respondents were asked to identify the most important environmental impacts. The relative importance of the impacts identified were calculated and ranked by the relative importance index. According to the results of the study, the respondents agreed that resource consumption group impacts ranked highest among the major impacts of construction activities on the environment in Ghana. The resource consumption group impacts were raw materials consumption, electricity consumption, water consumption and fuel consumption. Biodiversity impact was second followed by local issues impacts. The paper recommends that stakeholders in the construction industry should come up with special legislations, codes or standards relating to sustainable construction practices specific to Ghana’s construction environment and ensure proper and effective implementation.